Search for the lepton flavour violating decay τ- → μ-μ+μ- - Aaij, Roel; Adeva, B.; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; Esen, Sevda; Färber, Christian; et al. (Journal of high energy physics, 2015)
A search for the lepton flavour violating decay τ− → μ−μ+μ− is performed with the LHCb experiment. The data sample corresponds to an integrated luminosity of 1.0 fb−1 of proton-proton collisions at a centre-of-mass energy of 7 TeV and 2.0 fb−1 at 8 TeV. No evidence is found for a signal, and a limit is set at 90% confidence level on the branching fraction, B(τ− → µ−µ+µ−) < 4.6 × 10−8.
The LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, B. Adeva, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Färber, M. Fontana, E. Gersabeck, L. Grillo, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, M. Neuner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, M. Stahl, S. Stahl, U. Uwer, M. Vesterinen, R. Waldi, S. Wandernoth, D. Wiedner, C. Voß, A. Zavertyaev, A. Zhelezov, l. Zhong, [und 661 weitere]
Im Titel sind "-" und "+" hochgestellt
Gesehen am 06.10.2020